2016
DOI: 10.1177/0363546516674190
|View full text |Cite
|
Sign up to set email alerts
|

Biceps Disorder Rehabilitation for the Athlete: A Continuum of Moderate- to High-Load Exercises

Abstract: These findings may assist clinicians to select appropriate exercises to be used in the more advanced phases of nonoperative or postoperative rehabilitation of overhead athletes with biceps-related injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…1); pectoralis minor may be inhibited by performing ER, with preference in an open kinetic chain [49]; serratus anterior is more activated during elevation exercises than isolated protraction exercises [53]; rotator cuff activity is low during low-load closed-chain exercises such as bench or wall slides [48] (Figs. 2 and 3); infra-and supraspinatus activity is high during ER exercises [48]; subscapularis activity may be increased by performing flexionextension exercises in low elevation angles [54]; biceps activity is high during plyometric elevation exercises in supination [55]; exercises with an open hand favor middle trapezius and lower trapezius activity, whereas making a fist possibly increases rotator cuff activity [52,56]; the clinician may combine the above-mentioned guidelines in the individualized exercise program, based on several treatment goals, thereby resulting in a variety of specific exercises.…”
Section: How Do We Select the Appropriate Exercises?mentioning
confidence: 99%
“…1); pectoralis minor may be inhibited by performing ER, with preference in an open kinetic chain [49]; serratus anterior is more activated during elevation exercises than isolated protraction exercises [53]; rotator cuff activity is low during low-load closed-chain exercises such as bench or wall slides [48] (Figs. 2 and 3); infra-and supraspinatus activity is high during ER exercises [48]; subscapularis activity may be increased by performing flexionextension exercises in low elevation angles [54]; biceps activity is high during plyometric elevation exercises in supination [55]; exercises with an open hand favor middle trapezius and lower trapezius activity, whereas making a fist possibly increases rotator cuff activity [52,56]; the clinician may combine the above-mentioned guidelines in the individualized exercise program, based on several treatment goals, thereby resulting in a variety of specific exercises.…”
Section: How Do We Select the Appropriate Exercises?mentioning
confidence: 99%
“…However, the results of this exercise were obtained in only one study. 42 Therefore, this suggestion should be interpreted with caution. In addition, this review found that the UT was less active than the MT and LT during the supine pull-up with a pronated grip exercise.…”
Section: Discussionmentioning
confidence: 97%
“…Although pull-up exercises are not as common as push-ups in the clinical setting, it was found in this review that all 3 muscle ratios were excellent during half supine pull-ups with slings ( Figure 5C). 42 This exercise may be an option for the restoration of scapular muscle imbalance by selective strengthening of the MT, LT, and SA. However, the results of this exercise were obtained in only one study.…”
Section: Discussionmentioning
confidence: 99%
“…Between MVIC measurements of different muscles, 15 seconds of rest were provided. 18 Second, participants randomly performed 5 variations of bilateral elevation with external rotation: (1) open-hand position as reference exercise, (2) closed-hand (ie, making a fist) position, (3) dynamic bipedal squat, (4) static unipedal squat on the contralateral leg, and (5) dynamic unipedal squat on the contralateral leg (see Figure A through E and Table 1 for exercise descriptions). Comparison of exercises 1 and 2 will be referred to as ''altering upper extremity position,'' while comparison of exercises 1 and 3 through 5 is described as ''incorporation of the lower extremity.''…”
Section: Methodsmentioning
confidence: 99%
“…The color of the elastic band was determined in a pilot study (n ¼ 24) and based on sex and body weight. 18,19 Participants had to rate the exercise effort between 12 and 18 on a 20-point Borg scale, which is considered necessary for training strength. 20 Based on the results of the pilot study, the same elastic bands were used for all men (red) and for all women (yellow).…”
Section: Methodsmentioning
confidence: 99%